Fiction ou réalité : Les biographies de Constance Fenimore Woolson - Jeannine Hayat (Revue LISA)
Constance Fenimore Woolson (1840-1894) was an American novelist, famous toward the end of the 19th century. She was educated in the Great Lakes region, and her familiarity with the frontier gave her many subjects for her first stories published, among others, in Harper’s New Monthly Magazine and in the Atlantic Monthly. In 1873 she moved to Florida and began to feel inspired by the South, the Reconstruction after the war and the racial problem. She discovered Europe in 1880 and she met with Henry James in Florence. A strange friendship between the Master and the popular woman writer was to last until 1894. Leon Edel, Henry James’s biographer, supposed she felt an unrequited love for him. New feminist studies assert she was, on the contrary, independent and never asked literary figures for their help. Did she commit suicide or fall from a window by accident? Nobody knows. Contemporary novelists like David Lodge, Colm Toibin or Emma Tennant are puzzled by her relationship with Henry James.